Perceived government initiatives: Scale development, validation and impact on consumers' pro-environmental behaviour. (November 2021) - Mohanty, Pradeep Kumar; Patro, Archana; Harindranath, R.M.; Senthil Kumar, N.; Panda, Debadutta Kumar; Dubey, Ritesh
Abstract: Recent Government Initiatives towards popularising energy efficient appliances in India have created public consciousness about energy efficiency and cost-saving. This study examines the public perception towards energy policy and the subsequent consumer purchase behaviour towards energy efficient aplliances. The study developed a new scale on perceived government initiatives from consumers' perspective by exploring the social and psychological behaviour and subsequently operationalizing the construct. The reliability and validity of the developed construct, and their impact on consumers' pro environmental behaviour were estimated using maximum likelihood estimation. Public expectations from such government initiatives have been broadly categorized into four dimensions such as social influence, optimism, purchase preferences, and overall attitude. Overall findings reveal that the perceived government initiatives positively influences consumers' pro environmental behaviour. The study emphasizes the need for coordinated planning between manufacturers and the policy makers to further popularize energy efficient appliances among the public. Highlights: Energy Policy: exploring social & psychological behaviour of public perception. Dimensions: Public attitude, optimism, preferences, social influence. Public participation is a must for implementing the government initiatives. People prefer pragmatic approaches over the rational to enhance their livelihood. Holistic approach adoption by policy makers encourage proenvironmental behaviour.